Phenomenology of Hair Cutting Tradition Before the Wedding Process: An Analysis of `Urf and Value - Kaema, Muhammad Tolal; Yandi, Akmal; Badruzaman, Dudi; Efrinaldi, Efrinaldi (Sekolah Tinggi Agama Islam Solok Nan Indah, 2024)
Indonesian society has traditions rooted in religious values, customs and habits that are still characteristic of each ethnicity and region. One of the traditions that is still carried out today is cutting hair before the wedding process takes place. This study aims to analyze how the law of the tradition of cutting hair before the wedding process in a group of Minangkabau ethnic communities based on `urf, as well as the values contained in the procession. This research uses a qualitative method with the type of phenomenology, data sources are taken from ten informants through in-depth interviews individually selected by purposive sampling technique. In addition, researchers also made direct observations at all stages of the tradition process which is the focus of this study. All data were analyzed interactive Miles & Huberman technique. The research findings show that the tradition of cutting hair before the wedding process in terms of `urf is permissible and does not contradict the provisions of the Quran and hadith. Furthermore, there are two values contained in the tradition of the hair cutting procession i) purifying the bride and groom before the wedding, ii) strengthening the relationship between all family members. These findings have successfully established how the tradition of hair cutting before marriage in `urf is declared valid because it does not contradict Islam, then this tradition needs to be passed down from generation to generation because it contains noble values that benefit both bride and groom and family.